Study and Analysis of a Cooling System for Draught Drinks. - Clito Afonso (2014)
Draught refrigeration systems are usually available on restaurants, bars, etc., being responsible to cool down different kinds of beverage from the environment temperature down to 3 C. As they are installed in several thousand places and its operation runs for 24 h per day and per year, the knowledge of its performance is relevant for the energy consumption. Thus, one of these machines was fully instrumented with sensors to evaluate its behaviour. Additionally, it was used the EES software for simulations as well as tests were carried out in laboratory environment. Based on both results, strategies to improve the efficiency are discussed, namely the amount of ice present in the tank, the continuous operation of all the system that can be shorter in order to decrease the energy consumption and the CO2 emissions released by the power plants and the performance of the internal heat exchanger that presents an extremely low value.